Socio-ecological risk factors, explanatory models and treatment-seeking behaviours associated with Mseleni joint disease: a biocultural mixed methods study - Dinkele, Elizabeth Sarah (Department of Human Biology, 2022)
Mseleni Joint Disease (MJD) is a crippling osteoarthropathy of unknown aetiology endemic to southern African Bantu-language speakers in a remote region of Northern KwaZulu-Natal, South Africa. Effective management of MJD has been hindered by limited insight into risk factors, explanatory models or treatment-seeking behaviours in those affected. Until MJD is better understood, disability, unemployment and dependence on social assistance grants and family income for subsistence will remain a reality for those affected. A mixed methods study was conducted with the aims of examining risk factors, explanatory models and treatment-seeking behaviours associated with MJD. The distribution, differential diagnosis and treatment of MJD were statistically analysed using medical records (n=723), MJD-patient surveys (n=37) and a meta-analysis. Socio-economic and cultural risk factors were assessed from surveys (n=99) and census publications. Interviews with MJD patients (n=6), nurses (n=7) and doctors (n=9) were qualitatively analysed for themes pertaining to perceptions, experiences and treatment-seeking for MJD. A point prevalence of 9% was estimated. Women were nearly twice as likely to have MJD than men (OR= 1.89; p=0.03) and the likelihood of MJD increased almost three-fold in those older than 50 years (OR= 2.83; p<0.01). Age was a confounder of the association between gender and MJD, as the sample was skewed in the representation of elderly women. MJD was only detected in patients older than 35 years, indicative of a later onset age than previously reported. The prevalence of MJD in settlements along tar and concrete roads, with access to public transport but limited piped water was suggestive of environmental risk factors or differential access to hospital-based care. Explanatory models of MJD were supernatural (witchcraft or ancestral displeasure); natural (nutritional deficiencies, 'genetics' and/or environmental); and/or social (gender-based practices and lifestyle). MJD patients described supernatural and natural aetiologies, and conceptualised disability as an inevitable reality. Consequently, patients reported taking few measures to prevent joint immobility, focussing instead on immediate symptomatic relief. Psychosocial and systemic barriers to treatment were suggestive of a disconnect between traditional African healing and Western biomedicine. This work demonstrates the value of the biocultural approach in identifying spatial, ecological, social and cultural processes that shape population patterns of health and disease.